Jammers for mobile cellular systems applied to unauthorized UAVs - Lara, Karla Valentina de Freitas (2021)
This research aims to explore jamming on digital mobile systems, with an initial focus towards the 2G and Global System of Mobile Communications (GSM) technologies. The main goal is to develop a jammer with an efficiency and complexity greater than the existent ones, capable to better disrupt digital mobile systems. The study consists of an analysis of the different techniques of jamming, that can disrupt the mobile cellular system’s communication, through a series of simulations using the Software Defined Radio (SDR) and the GNU Radio ecosystem. The same techniques will then be studied and evaluated in real life scenarios in order to select which one is the best regarding spectral efficiency, energy and complexity. Finally, the jammer returning the best results will be the one chosen to contribute sustainably for the issue with flying drones on restrict areas, such as airports and residential zones, and thus, decrease the number of accidents which nowadays happen usually with this kind of aircrafts.